Exploring the potential of generative artificial intelligence in enhancing academic integrity - Md Nor, Nor Saadah; Mahri, Nurhafizah; Ahmad Nawawi, Nur Syahirah; Sarif Abdullah, Sharifah Nur Amirah (Centre for Islamisation, International Islamic University Malaysia, 2024)
The potential of generative artificial intelligence (AI) in enhancing academic integrity is a subject of growing interest and importance in education. AI’s role in academia is becoming more prominent as technology advances, leading to opportunities and challenges in preserving academic integrity. Generative AI (GenAI), a subset of artificial intelligence, can imitate original and authentic content, presenting a unique opportunity to support academic integrity efforts. To fully harness its potential, educators and institutions must understand the basics of generative AI and its educational applications. This understanding will prepare academia for the future of education, where AI can promote originality and creativity while maintaining academic honesty. This research aims to delve into the various objectives of applications of generative AI in education, such as personalised learning experiences, automated grading systems, and content generation for educational materials. This study aims to shed light on the potential of generative AI in enhancing academic integrity and provide insights that can guide educators, policymakers, and stakeholders in making informed decisions about integrating AI technologies into the educational landscape.